Hubungan Pengetahuan Ibu Tentang Pemberian Makanan Bayi dan Anak (PMBA) dengan Status Gizi Bayi Bawah Dua Tahun (Baduta) - Fatimah Sari; Evy Ernawati (Journal of Health (JoH), 2018)
Background: The paradigm of the first 1000 days of life is the period of conception and giving opportunities in saving the lives and future of children. Breast milk is recommended as one of the exclusive source of nutrition in the first 6 months. Nutrition deficiency is suspected due to a lack of understanding of parents on proper nutritious food or due to the influence of advertising. They want to break the cycle of malnutrition that causes stunting. Objective: This research aims to know the relationship of the level of knowledge of the feeding of infants and children (PMBA) with the nutritional status of infants under two years (BADUTA). Method: This research is using descriptive analytic method with cross-sectional approach. Research subjects were mothers who had Baduta in the village of Pandes Wedi Klaten Regency in Central Java. The way of determining the sample by the total sampling techniques. Instrument research using questionnaires conducted test validity and reabilitas. Analysis of data for the purpose of hypothesis testing using statistical tests Spearman Rho. Result: Mothers with good level of knowledge in feeding on baduta were as much as 100%. Whilst Baduta with good nutritional status were as much as 66.67%. Nutritional status of less baduta that is as much as 10 (33.33%). The results obtained bivariat relationship level of knowledge of mothers with nutritional Status Baduta the value of p = 0,272, since the p value > 0.05 (0,272 > 0.05) it can be stated there was no relationship between the level of knowledge of parents against the nutritional status of infants under two years of age. Conclusion: There is no relationship of the level of knowledge with nutritional status baduta with a value of p = 0.272.